2007
DOI: 10.1002/qj.5
|View full text |Cite
|
Sign up to set email alerts
|

Small scale mixing processes at the top of a marine stratocumulus—a case study

Abstract: A layer of intensive mixing (entrainment interface layer, [EIL]) at the top of marine stratocumulus under a strong inversion has been investigated with 10 cm resolution using an ultrafast thermometer (UFT-F; temperature), a particle volume monitor PVM-100A (liquid water content), and a fast forward scattering spectrometer probe (FFSSP; droplet spectra). Measurements were collected on board the NCAR C-130 aircraft during research flight RF05 of DYCOMS-II field study. The EIL consists of mutual filaments of clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 35 publications
(36 reference statements)
6
83
0
Order By: Relevance
“…Direct mixing between air from above the inversion and the quasi-adiabatic cloud is not common and the cloud-top entrainment instability criterion should not be applied to free tropospheric air and quasi-adiabatic cloud volumes. More detailed analysis of the small-scale structure of mixing by Haman et al (2007) confirms the presence of an entrainment interfacial layer and mixing between this layer and the cloud. A survey of LES of stratocumulus by Stevens (2002) showed that entrainment rates diagnosed from LES results can vary by up to a factor of two.…”
Section: Entrainment In Stratocumulusmentioning
confidence: 74%
See 1 more Smart Citation
“…Direct mixing between air from above the inversion and the quasi-adiabatic cloud is not common and the cloud-top entrainment instability criterion should not be applied to free tropospheric air and quasi-adiabatic cloud volumes. More detailed analysis of the small-scale structure of mixing by Haman et al (2007) confirms the presence of an entrainment interfacial layer and mixing between this layer and the cloud. A survey of LES of stratocumulus by Stevens (2002) showed that entrainment rates diagnosed from LES results can vary by up to a factor of two.…”
Section: Entrainment In Stratocumulusmentioning
confidence: 74%
“…Warner, 1955, 1969a, 1969b, Blyth et al, 1988Gerber et al, 2005Gerber et al, , 2008Burnet and Brenguier, 2007;Haman et al, 2007) tend to show that stratocumulus is only slightly diluted by entrainment, whereas cumulus is much more strongly diluted. In cumulus clouds the droplet number concentration is less reduced by entrainment than the liquid water content because the majority of droplets exhibit some evaporation.…”
Section: Homogeneous and Inhomogeneous Mixingmentioning
confidence: 96%
“…For example, during the DYCOMS-II experiment (e.g., Haman et al 2007) a similar approach led to the estimate of an entrainment interface layer from 0 to 70 m thick, based on high-resolution LW C and temperature measurements. It is important to recognize, however, that the ACTOS profiles should be interpreted somewhat differently because of the relative flight speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Large-eddy simulation (LES) demonstrates that this conditioned layer is almost always present above stratocumulus cloud tops and that its maintenance is related to 'local' shear effects due to convective eddies (Moeng et al 2005). High spatial resolution measurements have provided further characterization of what has been termed the "entrainment interface layer," consisting of filaments of clear and cloudy air over a wide range of sizes down to the instrument resolution of 0.1 m Haman et al 2007). Based on those measurements it was suggested that after multiple mixing events the entrainment interface layer becomes conditioned to the extent that there is near buoyancy match with the air at cloud top .…”
Section: Introductionmentioning
confidence: 99%
“…Data from in situ measurements (e.g., Caughey et al, 1982;Nicholls, 1989;Lenschow et al, 2000;De Roode and Wang, 2007) and the results of numerical simulations (e.g., Moeng et al, 2005;Yamaguchi and Randall, 2008) clearly indicate that the top of Sc is located below the capping inversion and does not directly interact with the FT above. The thickness of the EIL, related to the distance between the cloud top and inversion, varies from a few meters to a few tens of meters (e.g., Haman et al, 2007;Kurowski et al, 2009;Katzwinkel et al, 2012), and differs for different Sc cases (Carman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%